Key differences between chronic inducible and spontaneous urticaria - Bizjak, Mojca; Košnik, Mitja (Frontiers in Allergy, 2024)
IntroductionThe latest international EAACI/GA²LEN/EuroGuiDerm/APAAACI guideline for urticaria recommends limited laboratory testing for chronic spontaneous urticaria (CSU) and selective testing for only certain chronic inducible urticaria (CIndU) subtypes, though the rationale for these recommendations is poorly explained. This study aimed to improve the understanding of CIndU subtypes by comprehensively comparing their demographic, clinical, and laboratory characteristics with those of the better-characterized CSU.MethodsWe conducted a retrospective analysis of 567 patients (median age 41 years, 67% female) diagnosed with CSU, symptomatic dermographism (SD), cold urticaria (ColdU), cholinergic urticaria (CholU), and delayed pressure urticaria (DPU).ResultsOur findings revealed that patients with SD, ColdU, and CholU had lower levels of C-reactive protein (CRP), higher total serum immunoglobulin E (IgE) levels, and higher basophil counts compared to CSU patients. These subtypes also had distinct demographic and clinical features, such as a younger age of onset and a longer disease duration. In contrast, patients with DPU had significantly higher CRP levels and neutrophil counts compared to those with CSU.DiscussionThese findings highlight the heterogeneity among chronic urticaria subtypes, suggesting that a tailored approach to laboratory testing may be more effective. The distinct immunological and clinical features observed in CIndU subtypes suggest a need for subtype-specific diagnostic and therapeutic guidelines.